2010
DOI: 10.1111/j.1445-2197.2010.05209.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of spleen injuries: the current profile

Abstract: In Victoria, conservative management is the preferred approach in patients with minor (AIS = 2) to moderate (AIS = 3) splenic injuries. The low rates of embolization warrant further research into whether splenectomy is overused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Total splenectomy 61.7% was the commonest operation performed in our splenic injured patients. In the literature the rate range was 32% -72% [10,12,14,15,20]. Whereas Splenorrhaphy was practiced in 4.3% of our patients and this simulate others' findings [20,21], but lower than 19.2% in a Nigerian study [10].…”
Section: Operative Managementsupporting
confidence: 68%
“…Total splenectomy 61.7% was the commonest operation performed in our splenic injured patients. In the literature the rate range was 32% -72% [10,12,14,15,20]. Whereas Splenorrhaphy was practiced in 4.3% of our patients and this simulate others' findings [20,21], but lower than 19.2% in a Nigerian study [10].…”
Section: Operative Managementsupporting
confidence: 68%
“…While non-operative management of blunt splenic injury is a growing trend, and the use of splenic artery embolisation is commonplace in the literature, the under-utilisation of embolisation has been noted in other Australian tertiary trauma centres. Mikocka-Walus et al (2010) concluded that embolisation was under-utilised in Victorian trauma hospitals where only 17 of 300 patients presenting with blunt splenic injury received embolisation. Mikocka-Walus et al (2010) suggested that a reason for the under-utilisation of embolisation may be that patients with low-grade injuries are managed conservatively while patients with high-grade injuries and/or multiple abdominal injuries proceed to the operating theatre and were more likely to have a splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…While non-operative management of blunt splenic injury is a growing trend, and the use of splenic artery embolisation is commonplace in the literature, the under-utilisation of embolisation has been noted in other Australian tertiary trauma centres. Mikocka-Walus et al. (2010) concluded that embolisation was under-utilised in Victorian trauma hospitals where only 17 of 300 patients presenting with blunt splenic injury received embolisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing recognition of the role of the spleen in immunological function and awareness of overwhelming post-splenectomy infection (OPSI), atherogenesis and ischemic diseases, there has been an increasing trend towards NOM and splenic salvage procedure. [1] However, this policy change towards splenic conservation requires careful risk-benefit analysis in the face of potentially life-threatening hemorrhage from delayed splenic rupture and the possibility of transfusion-induced viral infections. Furthermore, the increasing availability of reliable and good quality radiological imaging, including ultrasound and computerized tomography (CT) scanning, has greatly improved the information available with regard to the nature of the splenic injury, and this may well help to identify the suitable patients for NOM, [2] but at the expense of radiation to the patient.…”
Section: Resultsmentioning
confidence: 99%